A Comparison of the Effects of Supervised versus Home Schroth Exercise Programs with Adolescent Idiopathic Scoliosis - Kadriye Tombak; İnci Yüksel; Umut Ozsoy; Yılmaz Yıldırım; Sezen Karaşin (MDPI AG, 2024)
(1) Background: Schroth exercise can reduce the deformity of the spine and improve the life quality and the body image of patients with adolescent idiopathic scoliosis (AIS). (2) Methods: The study began with 49 participants, aged 10-16 years old, who were diagnosed with AIS. At the end of the study, 37 patients were randomly assigned to either the Supervised (n = 19) or Home-Based Schroth Exercise Group (n = 18) and completed the study. Both groups were treated for seven days a week over twelve weeks. For all patients, body rotation measurements were performed with a scoliometer, surface asymmetry analysis was carried out using an Artec Eva 3D scanner, health-related quality of life was evaluated by the Scoliosis Research Society-22 (SRS-22) questionnaire, and the perception of the cosmetic deformity was assessed by the Walter Reed Visual Assessment Scale (WRVAS). All the measurements were repeated before and after the 12-week treatment. (3) Results: Post-treatment scoliometric measurements showed a significant decrease in body rotation in both groups (p < 0.05). Similarly, both groups observed significant positive changes in SRS-22 and WRVAS scores (p < 005). RMS values were statistically significant in both groups; the difference was only statistically significant in the thoracic anterior arm subparameter (p < 0.05). (4) Conclusion: The Schroth exercise for both groups with AIS improved body symmetry, quality of life, and body image.